2018
DOI: 10.1101/311563
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systematic survey of human tissue-specific gene expression and splicing reveals new opportunities for therapeutic target identification and evaluation

Abstract: Differences in the expression of genes and their splice isoforms across human tissues are fundamental factors to consider for therapeutic target evaluation. To this end, we conducted a transcriptome-wide survey of tissue-specific gene expression and splicing events in the unprecedented collection of 8527 high-quality RNA-seq samples from the GTEx project, covering 36 human peripheral tissues and 13 brain subregions. We derived a weighted tissue-specificity scoring scheme accounting for the similarity of relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 51 publications
3
30
0
Order By: Relevance
“…We used the patterns of expression of cell-type-specific genes to estimate the cellular composition of human tissues and organs from GTEx bulk tissue transcriptome data (version 6, 8555 samples, 31 tissues, 544 individuals) (The GTEx Consortium 2017). We used xCell (Aran et al 2017), using the sets of genes specific to epithelial, endothelial, and mesenchymal major cell types derived from EN-CODE, and specific to brain (neural) and blood derived from GTEx (Yang et al 2018) as signatures, and computed the enrichments of these cell types in each GTEx tissue sample (Supplemental Methods 8).…”
Section: Estimation Of the Cellular Composition Of Complex Organs Fromentioning
confidence: 99%
“…We used the patterns of expression of cell-type-specific genes to estimate the cellular composition of human tissues and organs from GTEx bulk tissue transcriptome data (version 6, 8555 samples, 31 tissues, 544 individuals) (The GTEx Consortium 2017). We used xCell (Aran et al 2017), using the sets of genes specific to epithelial, endothelial, and mesenchymal major cell types derived from EN-CODE, and specific to brain (neural) and blood derived from GTEx (Yang et al 2018) as signatures, and computed the enrichments of these cell types in each GTEx tissue sample (Supplemental Methods 8).…”
Section: Estimation Of the Cellular Composition Of Complex Organs Fromentioning
confidence: 99%
“…Our findings establish that blood mQTLs are robust and reproducible, supporting their generalizability across age groups, ancestries, disease status, and DNA sample source, and offer a valuable source for future studies examining blood mQTLs. Recent studies have identified different sets of differential DNAm patterns in various tissue types [21,22], and previous epigenomic and transcriptomic studies in IBD suggest that disease-relevant tissue samples are needed to develop precise biomarkers for the disease subtypes [5,[23][24][25]. Our findings show that among genome-wide-significant mQTLs, genetic influences on DNAm are generally consistent across blood and ileum, even among IBD SNPs and CD-associated CpG sites.…”
Section: Discussionmentioning
confidence: 51%
“…Tissue-specificity is a recognized yet underutilized resource particularly in drug discovery ( Yang et al, 2018 ; Yao et al, 2018 ; Ryaboshapkina and Hammar, 2019 ). The lack of a detailed understanding of the underlying gene regulation is clearly a major roadblock ( Sonawane et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue-specificity is a recognized yet underutilized resource particularly in drug discovery (Yang et al, 2018;Yao et al, 2018; Supplementary Table D. Ryaboshapkina and Hammar, 2019).…”
Section: Chronic Dosingmentioning
confidence: 99%